2022
DOI: 10.30762/jeels.v4i1.333
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Writing Anxiety of Indonesian EFL College Learners

Abstract: This study aims at analyzing the writing anxiety of English students of an Islamic State College in East Java, Indonesia. This study described the levels, dominant type, and main factors of writing anxiety of the English students. Fifty English students at the fourth semester participated in this study. Two closed-ended questionnaires, Second Language Writing Anxiety Inventory (SLWAI) proposed by Cheng, and Causes of Writing Anxiety Inventory (CWAI) proposed by Rezaei and Jafari were employed to collect the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 4 publications
21
51
1
Order By: Relevance
“…13. This finding is in support with the finding of Wahyuni and Umam's study [3], Ariyanti's study which suggest that Indonesian EFL learners mostly suffered from a high level of writing anxiety but is in contrast with the finding of Sundari's and Febriyanti's study which suggests that Indonesian EFL learners do not feel very anxious when writing English. However, this kind of phenomenon, that many students suffer from a high level of writing anxiety is not only the typical of Indonesian learners since the study of Jennifer and Ponniah in India [15], Rezaei and Jafari in Iran [13] also suggest the similar things.…”
Section: B Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…13. This finding is in support with the finding of Wahyuni and Umam's study [3], Ariyanti's study which suggest that Indonesian EFL learners mostly suffered from a high level of writing anxiety but is in contrast with the finding of Sundari's and Febriyanti's study which suggests that Indonesian EFL learners do not feel very anxious when writing English. However, this kind of phenomenon, that many students suffer from a high level of writing anxiety is not only the typical of Indonesian learners since the study of Jennifer and Ponniah in India [15], Rezaei and Jafari in Iran [13] also suggest the similar things.…”
Section: B Discussionsupporting
confidence: 83%
“…The study of Ariyanti for example found that many learners were suffering from a high level of writing anxiety [2]. Another study as written by Wahyuni and Umam also found out that more than half of their research respondents suffered from a high writing anxiety [3]. This condition is very unfavourable because anxiety has been proven to negatively correlate with learning achievement [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the result of the study conducted by Wahyuni & Umam (2017) which shows that linguistics difficulties and negative comments are the two main causes of the students' fear and anxiety to writing in English. These fear and anxiety, if not solved properly, might affect the students' attitude toward writing in English.…”
Section: Discussionsupporting
confidence: 78%
“…Basically, these facts appeared on the students' reasons because of their negative perception toward writing. Therefore, they experienced writing anxiety (Kurniashi, 2013;Huwari & Aziz, 2011;Fareed et al, 2016;and Wahyuni & Umam, 2017), in which, the factors that cause writing anxiety of Indonesian EFL students were difficulties in linguistics, worry of teachers' comments negatively, inadequate writing technique and practice, lack of topic knowledge, and time pressure (Kurniashi, 2013 andWahyuni &Umam, 2017). Additionally, low ability and writing anxiety of students were pressured by some factors they are untrained writing instructors, ineffective teaching methods of writing, insufficient system of writing examination, lack of reading and writing practice, big classes, low motivation, and limited ideas (Fareed et al, 2016).…”
Section: E Discussionmentioning
confidence: 99%